Czesława Znamierowskiego koncepcja „redukcji indywidualizującej" - Czepita, Stanisław (Wydział Prawa i Administracji UAM, 1987)
The article is a recollection (sec. 2) and a critical analysis (sec. 3) of the conception of „individualising reduction" formulated by the eminent Polish philosopher, sociologist and lawyer Czesław Znamierowski (1888 - 1967). According to the said conception, a necessary condition for the scientific character of a statement describing the properties (behaviour) of a given social group is that such a statement is to be tantamount to a set of sentences describing the properties (behaviour) of individuals constituting that group and its structure. Such „reduction" of a statement concerning the group to the statements concerning individuals constituting the group and its structure is particularly difficult in cases of statements describing conventional acts of a group. Besides, the article stresses the importance of Cz. Znamierowski's conception as an attempt to synthesize selected elements of positivistic and antipositivistic paradigm of sociological reflection.
Czesław Znamierowski's conception of "indyvidualising reduction"